2004
DOI: 10.1002/eat.20034
|View full text |Cite
|
Sign up to set email alerts
|

Eating behavior disorders in Chilean infants

Abstract: EBDs in Chilean infants are observed during the first months of life and are associated with a lower birth weight, shortened exclusive breast-feeding, maternal history of EBD during their infancy, and lower physical growth. Mothers of children with EBD frequently feel that their maternal role is difficult and unsatisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…In contrast, poor engagement may have a comparable negative impact on health, nutrition, and general mealtime success, but may be harder for parents to explain and/or demonstrate in a clinical setting, and thus they may be more anxiety provoking for parents. This supports the high levels of parental stress, anxiety, and deficits to parental self-efficacy observed in parents of children with problematic or disordered feeding (e.g., Feldman, 2004;Greer et al, 2008;Lindberg, Bohlin & Hagekull, 1994;Sanchez & Castillo-Duran, 2004). Such a situation may also lead parents to over-report the overt and more easily described behaviours in the clinical interview, reinforcing the over-reliance on these types of behaviours in clinical identification.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In contrast, poor engagement may have a comparable negative impact on health, nutrition, and general mealtime success, but may be harder for parents to explain and/or demonstrate in a clinical setting, and thus they may be more anxiety provoking for parents. This supports the high levels of parental stress, anxiety, and deficits to parental self-efficacy observed in parents of children with problematic or disordered feeding (e.g., Feldman, 2004;Greer et al, 2008;Lindberg, Bohlin & Hagekull, 1994;Sanchez & Castillo-Duran, 2004). Such a situation may also lead parents to over-report the overt and more easily described behaviours in the clinical interview, reinforcing the over-reliance on these types of behaviours in clinical identification.…”
Section: Discussionsupporting
confidence: 55%
“…This suggests that reduced food intake is a key characteristic of disordered feeding behaviour in childhood, and indeed an ARFID diagnosis will be unequivocal in children requiring supplementary or total tube-feeding in the absence of physical cause. However, a great many additional psychological, social, and emotional factors have also been associated with disordered child feeding (Berlin et al, 2009;Black, 1999;Bryant-Waugh et al, 2010;Chatoor et al, 1998;Piazza, 2008;Sanchez & Castillo-Duran, 2004;Stein et al, 1999). This suggests that neglecting other factors in favour of physical attributes omits a population of children with disordered feeding from assessment and treatment, simply because they are managing, at that time, to maintain weight/growth, often via alternative, undesirable methods such as excessive milk intake or high calorie-low nutrient diets (Bryant-Waugh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Results suggest that sitting at the table, about the same time every day and eating the same food together with the rest of the family shaped a favorable environment that was associated with appropriate feeding behaviors in the present study. Existing literature verifies that children who lack a structured and consistent meal routine are more likely to exhibit feeding problems [ 9 , 57 , 68 , 69 ]. In addition, as children learn to eat through observation and role-modeling by family members, this finding highlights the importance of systematically exposing the child to positive eating patterns and integrating into the feeding environment of the rest of the family [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, prenatal nutritional background and early nutritional measurements, were not found to be significantly associated with 2009 SIMCE outcomes and this does not agree with the results of other investigators [34]; the exception to these results was the negative correlation found for breastfeeding and MSA in 2010 5ESG school-age children. This could be explained because breastfeeding duration tends to be longer in families of the low SES in whom SA is significantly lower than in families of the high SES [82]. Although some authors report significant associations between breastfeeding, cognition and brain size, others emphasize that this association can be explained largely by socio-demographic factors, parental lifestyles and maternal intelligence [40,8285].…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained because breastfeeding duration tends to be longer in families of the low SES in whom SA is significantly lower than in families of the high SES [82]. Although some authors report significant associations between breastfeeding, cognition and brain size, others emphasize that this association can be explained largely by socio-demographic factors, parental lifestyles and maternal intelligence [40,8285].…”
Section: Discussionmentioning
confidence: 99%